Ilang Kuwentong Radyo ni Tiya Dely - Magpayo, Fidela “Tiya Dely” (Plaridel Journal of Communication, Media, and Society, 2007)
Established in 2004 by the University of the Philippines (U.P.) College of Mass Communication, the annual U.P. Gawad Plaridel is the sole award given in the U.P. System to outstanding Filipino media practitioners who have excelled in any of the media (print, radio, film, television, and new media) and have performed with the highest level of professional integrity in the interest of public service. The award is named after Marcelo H. del Pilar (nom de plume, Plaridel), the selfless propagandist whose stewardship of the reformist paper La Solidaridad helped crystallize nationalist sentiments and ignite libertarian ideas in the 1890s. Like Plaridel, the recipient of the award must believe in the vision of a Philippine society that is egalitarian, participative, and progressive, and in media that are socially responsible, critical and vigilant, liberative and transformative, and free and independent. Eugenia Duran-Apostol received the first U.P. Gawad Plaridel in 2004 for her contributions to print media. Rosa Vilma T. Santos-Recto (Vilma Santos) was the second U.P. Gawad Plaridel awardee for film in 2005. For the year 2006, the third U.P. Gawad Plaridel was awarded to Fidela “Tiya Dely” Magpayo. According to the citation that was given to her, she pursued in the last seven decades “the highest professional standards in all aspects of her work”. She also introduced and promoted Filipino songs as singer and radio producer in the 1930s and 1940s, at a time when there was a preponderance of American music and the country was a direct colony of the United States. Since the Commonwealth Period when Filipino was proclaimed the national language, Magpayo has helped propagate it through radio. She also promoted Filipino values “through the discussions and the advice she gave her radio listeners.” Overall, she helped define “Filipino cultural identity...through her excellent work as radio host, newscaster, singer, writer, and producer.” As the 2006 U.P. Gawad Plaridel awardee, Magpayo delivered this lecture during the U.P. Gawad Plaridel Paggawad at Lektyur on July 4, 2006 at the U.P. Film Institute Cine Adarna (formerly U.P. Film Center). More than 1,000 people attended the event, among them U.P. Diliman Chancellor Sergio S. Cao, National Artist for Sculpture Dr. Napoleon V. Abueva, then Lipa Mayor and 2005 U.P. Gawad Plaridel awardee Vilma Santos, faculty and students of the University of the Philippines (Diliman), Miriam College, University of the East (Manila), Polytechnic University of the Philippines, Far Eastern University, and St. Scholastica’s College.